Optimization of model of local mechanical injury of brain hemispheres - Novikov, Ruslan (Ukrainian Neurosurgical Journal, 2014)
The purpose. To develop, analyze and implement optimized model of local mechanical injury of brain hemispheres for focal neurological symptoms study. Materials and methods. In two groups of animals brain hemispheres injury was modeled. Animals in the 1st group were injured (open penetrating local brain injury) through the burr hole. After beam-walking test and lacks revealing the model was optimized. In animals of the 2nd group open penetrating local brain injury was modeled through the burr hole with visualization. Results. In the resulting model decrease of bleeding probability, wide burr hole limit negative effects of posttraumatic edema of the injured brain area. Conclusions. A new model of brain injury was developed. A low variability of functional deficits in animals of group 2 was found.